2020
DOI: 10.1016/j.resuscitation.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of in-hospital cardiac arrest in patients with COVID-19 in New York City

Abstract: Cardiopulmonary resuscitation (CPR) in patients with in-hospital cardiac arrest (IHCA) has been associated with poor overall survival and neurologic recovery. 1 The coronavirus 2019 (COVID-19) global pandemic carries a high mortality rate with high risk of cardiopulmonary arrest. 2 Clear policies for crisis standards of care and CPR are essential in light of limited Intensive Care Unit (ICU) resources and aerosolized transmission among code team members. 3 There is limited literature regarding the survival out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 4 publications
(6 reference statements)
7
66
1
3
Order By: Relevance
“…Similarly, poor outcomes were demonstrated in a cohort of 31 patients with COVID-19 suffering cardiac arrest at a New York City institution; 42% of patients achieved ROSC while no patient survived to hospital discharge. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, poor outcomes were demonstrated in a cohort of 31 patients with COVID-19 suffering cardiac arrest at a New York City institution; 42% of patients achieved ROSC while no patient survived to hospital discharge. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Decreased survival has been demonstrated among COVID-19 patients with IHCA as well as out-of-hospital cardiac arrest (OHCA). 7 , 11 , 12 Cardiac arrest among COVID-19 patients is more likely to be related to a non-shockable rhythm; a known factor associated with worse prognosis. 6 , 11 In OHCA, the rate of bystander CPR has been demonstrated to be significantly lower with delayed emergency medical arrival by contrast to the pre-pandemic period potentially explaining worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A single center study from New York City that included 31 patients with in-hospital cardiac arrest found that no patient survived to hospital discharge. 3 As a result of the lack of comprehensive data on outcomes after in-hospital cardiac arrest in patients with covid-19, implementation of DNACPR (do not attempt cardiopulmonary resuscitation) policies in this setting has been controversial. Some have argued that DNACPR should be considered when the supply of intensive care unit beds is limited and also owing to the risk of covid-19 transmission to healthcare workers during cardiopulmonary resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence gathering related to in-hospital cardiac arrest outcomes for COVID-19 patients is ongoing. Current studies have demonstrated outcomes for COVID-19 positive cardiac arrest cases range from 13.2% to 42% ROSC rate 47 , 48 , with one study in Wuhan, China reporting a 2.9% survival at 30 days. 47 However, a case series in USA reported no patients survived to hospital discharge .…”
Section: Introductionmentioning
confidence: 99%